Elevated tanks effect on transient pressures: case study - Moustafa S. Darweesh (IWA Publishing, 2021)
Elevated tanks are an integral part of the water supply networks. This paper highlights the effect of elevated tanks' location and size on the transient pressures resulting from the sudden failure of pumps. A comparison between the impact of elevated tanks and air vessels on the water hammer was also performed. The Bentley HAMMER model was first validated then applied to analyze the unsteady flow within an actual distribution network. The results display that the elevated tanks have a considerable effect on the surge pressures, where they improve the extreme pressures effectively at and around them, but they cannot fully protect the system from the water hammer risks, as there are still relatively large negative pressures at some distant junctions. Besides, as the tank capacity increases, the surge pressures increase slightly. In our case study, the best location of the elevated tank is at the network extremity and then at the pumping stations, since the minimum pressures improve by 67 and 54%, respectively. Although the present case study may differ from other supply systems, the obtained results can provide an indication of the elevated tanks' role in alleviating undesirable water hammer effects. Highlights This paper highlights the effect of elevated tanks’ location and size on the water hammer pressures.; A comparison between the impact of elevated tanks and air vessels was also performed.; The Bentley HAMMER model was validated and then applied to analyze the unsteady flow within an actual distribution network.; The gained results can give an indication about the effect of elevated tanks on the transient pressures.;